PENINGKATAN KETERAMPILAN MENULIS PUISI DENGAN MENGGUNAKAN MODEL PEMBELAJARAN EXAMPLE DAN NON-EXAMPLE SISWA KELAS X SMA NEGERI 10 KOTA TERNATE - Sibua, Sulami; Rahmadhany, Firdha (Jurnal Bilingual, 2020)
This research was conducted wiht the aim to find out how the students ability in writing poetry in class X SMAN 10 Ternate city and how to improve the ability to write poetry using the example and non-example models of grade X students of SMAN 10 ternate city. The methoud used in this research is descriptive quantitative and the instruments used are observation, interviews, tests and documentation.Based on the results of the studi, poetry writing skills improvement using example and non-example models class X students of SMAN 10 Ternate city consisting of 25 students can be seen that students are able writing poetry using model example and non-example, this is known from the results of research that there are worksheets on the pretest and postets which have increased, in the pretest and postest which have in creased, in the pretest with atotal value of 1.005 with and average value of 40,2 whereas the results of the posttest in the write poetry using the example and non-example models class X students of SMAN 10 Ternate city, with a value of 1.550 demgas an average value of 63,6 as manyÃ‚Â  23 students 68% have achieved (KKM) from the initial test results of 17 studens 92 % did not reach (KKM).